Development of an experimental setup for propeller performance measurements - Pugna Andreea; Hrab Călin; Hînsa Liviu-Nicolae; Hopârtean Andrei; Giurgea Corina-Maria; Marcu Lucian (E3S Web of Conferences)
With the increasing demand for efficient and adaptable unmanned aerial vehicles (UAVs), optimizing propeller performance has become essential to enhancing energy efficiency and thrust. This study introduces a compact, cost-effective experimental setup designed specifically for testing drone propellers on a small scale, making it accessible for both research and educational applications. The setup integrates off-the-shelf components, including a brushless motor controlled by an electronic speed controller (ESC), a load cell for precise thrust measurement, and a custom-built current sensor for power consumption analysis. The experimental set-up enables real-time data acquisition and evaluation of propeller performance across various operating speeds. By testing two commercial propellers—a two-blade and a three-blade design—the setup demonstrates its ability to analyze thrust and efficiency trends effectively. This innovative framework bridges the gap between theoretical studies and practical UAV applications, providing a versatile and scalable platform for advancing UAV propulsion research.